2022
DOI: 10.1021/acsanm.2c02418
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic Self-Cleaning Composite of a Metal–Organic Framework with Polypropylene Fabric for Efficient Removal of Oils from Oil–Water Mixtures and Emulsions

Abstract: Here, we report a metal–organic framework (MOF) [Hf6O4(OH)4(TFNDC)6]·6H2O·2DMF [SHMOF, where TFNDC = 1-(2,2,2-trifluoroacetamido)­naphthalene-3,7-dicarboxylate], which possesses excellent chemical and thermal stability along with remarkable hydrophobic characteristics. The hydrophobic SHMOF was used for in situ coating on the polypropylene (PP) fabric to make a superhydrophobic SHMOF–PP fabric composite. The immobilization of nanocrystalline particles of SHMOF creates a nanoscale hierarchy that enhances the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…To work out an easy and ecologically sound solution, numerous materials have been developed to separate oil–water mixtures employing superhydrophobic and superhydrophilic materials. 1 The superhydrophobic absorbent or membrane materials used for oil–water separation are metal mesh-based membranes, 2 sponge-based composites of fluorinated linkers, 3 fluorinated polymers, and aerogel materials. 4 Metal-based membranes have the drawback of corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…To work out an easy and ecologically sound solution, numerous materials have been developed to separate oil–water mixtures employing superhydrophobic and superhydrophilic materials. 1 The superhydrophobic absorbent or membrane materials used for oil–water separation are metal mesh-based membranes, 2 sponge-based composites of fluorinated linkers, 3 fluorinated polymers, and aerogel materials. 4 Metal-based membranes have the drawback of corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…The results have demonstrated that the separation efficiency of the PDMS-GR-Cu foam was very high, exceeding 99% for the tested oils and organic solvents with high flux rates (6216–11 700 L m –2 h –1 ) that are comparable or higher compared to the other fabricated filters (Figure b and Table S3). Although other oil–water separators exhibit superior separation performance, they do not provide any mechanism to kill adherent bacteria, which may lead to the loss of their permeate flux, limiting their use in bacteria-contaminated environments . The foams were further examined for reusability and separation efficiency by taking chloroform as a model pollutant since both are characteristics necessary for practical application.…”
Section: Results and Discussionmentioning
confidence: 99%
“…25 These show great potential for versatile oil–water separation but still have the disadvantages of high cost and low throughput. 26…”
Section: Introductionmentioning
confidence: 99%
“…25 These show great potential for versatile oil-water separation but still have the disadvantages of high cost and low throughput. 26 In recent years, the COVID-19 pandemic has created environmental challenges induced by the extensive use of face masks as more than 130 billion waste masks are disposed of globally every month. 27,28 Most waste masks are sent to landll or burned at high temperatures but both of these methods have negative environmental impacts.…”
Section: Introductionmentioning
confidence: 99%